The Act Of Complimenting In Malaysian English - Ahmad, Ummul Khair; Koh, Ming Ai (2010)
Complimenting is a very interesting speech act to look at because different cultures draw different assumptions when it comes to giving and receiving compliments. Studies such as Yu’s (2005) and Chiang and Pochtrager’s (1993) have shown that people from different cultures give and respond to compliments differently. Therefore, the purpose of this research is to find out how the giving and receiving of compliments are done among English speaking Malaysians. The method used for this research was the recording of naturally occurring casual conversations which was then transcribed and broken into individual tokens. Results show that although other Asian cultures have the tendency to reject the compliment, English speaking Malaysians mostly accept the compliment given, but at the same time they also shift or erode the force of the compliment to avoid self-praise. The implication of this research is that there are many ways to respond to compliments and still be polite. By teaching the ways to respond to compliments, teachers can expose the students to ways and means of using language beyond achieving the typical communicative goals.